Improved sine cosine algorithm for large-scale optimization problems - ZHANG Chao; YANG Yi (Shenzhen Daxue xuebao. Ligong ban)
Aiming at the shortcomings of the sine cosine algorithm (SCA) in solving the large-scale optimization problems, such as low accuracy, slow convergence speed, and being easy to fall into the dimension disaster, we propose an sine cosine algorithm with Lévy flight (SCAL). By using the element-by-element multiplication of the Lévy flight distribution with the individual position vector of sine and cosine population, the characteristics and information of Lévy flight distribution are integrated into the individual information, so that it can possess the characteristic of random walk of Lévy flight and enhances the ability of local exploitation to escape from local extremum. A novel nonlinear parameter adjustment method based on spatial distance is adopted to balance the local exploitation and global exploration, which improves the convergence speed of the algorithm. On 14 classic test functions with dimensions of 100, 1 000 and 5 000 respectively, SCAL is compared with five swarm intelligence algorithms including SCA, flower pollination algorithm (FPA), particle swarm optimization (PSO) algorithm, sparrow search algorithm (SSA) and whale optimization algorithm (WOA). The experimental results indicate that SCAL has a significant advantage over the five swarm intelligence algorithms in terms of convergence accuracy, convergence speed and robustness. Compared with the improved wolf pack algorithm (IWPA), the improved flower pollination algorithm (IFPA), the improved whale optimization algorithm (IWOA), and the modified whale optimization algorithm (MWOA), which are suitable for solving large scale optimization problems, it is found that the overall optimization result of SCAL is better than the comparison algorithms and thus demonstrate that the proposed algorithm has the obvious advantages and competitiveness for solving large-scale optimization problems.